The Impact of Internal Values, Green Attitudes, and Norms on Green Consumer Behavior in Jakarta - Tengku Muhammad Zikrie Maulana; Heri Fathurahman (Review of Multidisciplinary Academic and Practice Studies, 2026)
Purpose: This study aims to analyse the influence of Internal Values, Green Attitudes, and Subjective Norms on Green Customer Citizenship Behaviours (GCCB) among electric vehicle (EV) consumers in Jakarta, with a particular focus on the mediating role of green attitudes. Research methodology: A quantitative research design was employed using Partial Least Squares–Structural Equation Modelling (PLS-SEM) with SmartPLS version 4.0. Data were collected through an online questionnaire from 105 electric vehicle users domiciled in Jakarta, aged at least 18 years, and having used electric vehicles for more than twelve months. Results: The findings reveal that internal values have a positive and significant effect on green attitudes. Furthermore, green attitudes significantly influence green customer citizenship behaviour and were found to mediate the relationship between internal values and GCCB. In addition, subjective norms have a significant positive effect on both green attitudes and green customer citizenship behaviour, indicating the importance of social influence in encouraging pro-environmental behaviours among EV consumers. Conclusions: This study concludes that internal values and subjective norms play a crucial role in shaping green attitudes, which subsequently foster green customer citizenship behaviour among electric vehicle users in Jakarta. Limitations: The study is limited by its relatively small sample size and its focus on a single urban area, which may limit generalisability. Contribution: This research contributes empirical evidence to the literature on sustainable consumer behaviour by highlighting the mediating role of green attitudes and the importance of social norms in promoting green customer citizenship behaviour in the context of electric vehicle adoption